Detection of SAP genes in Candida albicans isolated from oral candidiasis in cancer patients - Majid kadhim Aboud Alshibly; Zahraa Khudhair Abbas Al-Khafaji (Al-Qadisiyah Journal of Pure Science, 2018)
Four types of the genus Candida were diagnosed in patients cancer, It is C. albicans ,C dublineinsis, C. glabrata  and C .kruse  in percentage 41(41) %,22(22%),19(19%) ,12(12%) Respectively. and  two types of yeasts were identified In the healthy people.it is C.albicans and C.glabrata by 22% (22%) and 2(2%) respectively .There were significant differences in the rate of white blood cells among males and females In cancer patients, and there were  significant differences between infected and healthy individuals, both male and female. There was a significant reduction in the rate of white blood cells in infected persons (males and females) There was a significant reduction in the rate of white blood cells in infected persons (males and females) compared to healthy people, as for protein production in C. albicans isolated from patients the number of positive samples to test was 40 (97.5%) while the negative samples were 1 (2.4%), while in C. albicans isolated from healthy persons the number of samples that gave positive result for testing are 13 (59%) while the negative samples to test were 9 (40.9%). It has also been detected   gene expression of (SAP1, SAP2, SAP3, SAP4) genes using Real-time PCR technology for some isolates before and during infection yeast cells  to epithelial, and the results were high production  rate of gene expression for the treatment T for all the genes of virulence factors (SAP1, SAP2, SAP3, SAP4) for treatment C and high Significant difference at the level of the probability P â‰¤ 0.01.And also back to us during the study there is a difference in gene expression of genes SAP family (SAP1, SAP2, SAP3, SAP4) for the treatment of T, where the gene scored (SAP1) the highest rate of gene expression and the amount (92.244+15.88358). followed by the gene (SAP4) rate (71.766 +10.42177) and after the gene (SAP3) rate (64.828+ 3.48543), while the gene record (SAP 2) the lowest rate at which gene expression (24.975+ 4.38852).